Interferon-γ promotes phagocytosis of Cryptococcus neoformans but not Cryptococcus gattii by murine macrophages. Issue 12 (December 2015) - Ikeda-Dantsuji, Yurika; Ohno, Hideaki; Tanabe, Koichi; Umeyama, Takashi; Ueno, Keigo; Nagi, Minoru; Yamagoe, Satoshi; Kinjo, Yuki; Miyazaki, Yoshitsugu
Abstract: Among invasive fungal infections, cryptococcosis caused by inhalation of Cryptococcus neoformans or Cryptococcus gattii is particularly dangerous because it can disseminate to the central nervous system and cause life-threatening meningitis or meningoencephalitis. Previous reports described significant differences in the histopathological features of C. neoformans and C. gattii infection, such as greater pathogen proliferation and a limited macrophage response in mouse lung infected by C. gattii. To elucidate the difference in pathogenicity of these two Cryptococcus species, we investigated the interaction of C. neoformans and C. gattii with murine macrophages, the first line of host defense, by confocal laser microscopy. Only thin-capsulated, and not thick-capsulated C. neoformans and C. gattii were phagocytosed by macrophages. Preactivation with interferon-γ increased the phagocytic rate of thin-capsulated C. neoformans up to two-fold, but did not promote phagocytosis of thin-capsulated C. gattii . Lipopolysaccharide preactivation or Aspergillus fumigatus conidia co-incubation had no effect on internalization of thin-capsulated C. neoformans or C. gattii by macrophages. Phagocytosis of live thin-capsulated C. neoformans, but not that of live thin-capsulated C. gattii, induced interleukin-12 release from macrophages. However, phagocytosis of heat-killed or paraformaldehyde-fixed thin-capsulated C. neoformans did not increase IL-12 release, showing that the internalization of live yeast is important for initiating the immune response during C. neoformans −macrophage interactions. Our data suggest that macrophage response to C. gattii is limited compared with that to C. neoformans and that these results may partially explain the limited immune response and the greater pathogenicity of C. gattii .